Latin American migrants' transit/ions and sexual agency reconfigurations - Ríos-Rivera, Abril (Frontiers in Human Dynamics, 2026)
This paper explores how gender-diverse migrants negotiate their sexual agency as they navigate migration structures, transiting sexual and geographical states of nepantla (in-betweenness). Following a transnational life-course approach, this paper situates gender-diverse migrants' sexual agency within the broader context of their lives, across origin and changing spaces of transit and destination. Employing qualitative data from photovoice workshops and individual interviews conducted in Tapachula, and Tijuana, Mexico, the research reveals intricate intersections between migration, sexuality, and identity change. Migrants' narratives highlight early experiences of non-conforming gender expressions that often led to rejection and violence, driving individuals toward survival migration. The findings illustrate how migration impacts identity transitions and affirmations, with new environments presenting both opportunities and obstacles in asserting sexual agency. Migrants' agential negotiations within restrictive migration structures revealed strategic compliance, as well as the active deployment of agency maximizing strategies including alliances with other migrants and organizations. As migrants transit nepantla, navigating geographical and gendered mobility, migration governance structures and restrictions, they also build solidarity networks and find innovative ways to negotiate and assert their agency. This paper contributes to ongoing scholarly debates around sexual migration and the sexuality of migration research angles offering a nuanced understanding of sexual agency and identity change in migration, while emphasizing the need for further research into the intersectional experiences of gender-diverse migrants.